Pengaruh Perubahan Nilai Tukar Rupiah, Tingkat Inflasi, dan Indeks Bursa Internasional Terhadap Indeks Harga Saham Gabungan (IHSG) di Bursa Efek Indonesia (BEI) - Keken Setiawan; Erly Mulyani (Jurnal Ecogen, 2020)
This research aimed to know how the effect of Rupiah Exchange Rate, inflation rate, and international Exchange Index towards Composite Stock Price Index (CSPI). The independent variables of this study are Rupiah Exchange Rate (X1), Inflation rate (X2), Dow Jones index (X3), Nikkei 225 index (X4), and Hang Seng index (X5). The Sample was based on monthly time series data from January 2014 to December 2018, with documentation data collection technique from Bank Indonesia and Yahoofinance.com publication. Analytical techniques used were linier regression, classical Assumtions, determination coeffisient test (R2), for hypothesis test used F-test and t-test with significance level of 5%. The results of this indicate that the value of cooficient of determination (R2) 0,901 which means independent variables affect the dependent variable 89,2% and the rest is 10,8% influenced by other variables outside this study. The result of t-test shows that the Rupiah Exchange Rate and Nikkei 225 index have not significant and negative effect on Composite Stock Price Index (CSPI), Inflation rate have significant and negative effect on Composite Stock Price Index (CSPI), Dow Jones index and Hang Seng Index have significant and positive effect on Composite Stock Price Index (CSPI). Keywords: composite stock price index (cspi), rupiah exchange rate, inflation rate, dow jones index, nikkei 225 index, and hang seng index